Synthesis, characterization and application of N-substituted and C-substituted nickel cyclam cataylsts in hydrodehalogenation reactions - Townsend, James Alan (Kansas State University, 2009)
Highly toxic aromatic halogenated compounds such as PCB’s, PCDF’s and PCDD’s act as persistent organic pollutants and can bio-accumulate. These compounds are highly stable to oxidation, reduction and thermal degradation. Current remediation technologies are expensive and can cause the formation of even more toxic byproducts. It is clear that an environmentally friendly and inexpensive remediation technology is required. Our goal was the synthesis of dehalogenation catalysts incorporating aromatic side arms for the pre-concentration of the substrates to the catalysts. We envisioned that aromatic side arms would allow the aggregation of catalyst and substrate to form a pre-complex that would enhance rates of dehalogenation. Rapid and stereochemically predictable synthesis of N and C functionalized nickel cyclam complexes were a priority for this project. Synthesis of N-functionalized cyclam molecules and subsequent metal incorporation proceeds smoothly to form trans(III) nickel cyclam complexes. However longer reaction times, initiation periods and short catalyst lifetimes made these complexes unsuitable for long-term study. Cyclization of dipeptides and tetrapeptides using a metal template in basic conditions led to the formation of cyclopeptide nickel complexes with stereochemistry retained from the peptide precursors. Free cyclopeptides could be isolated from the nickel complexes by treatment with HCl. Cyclopeptides are reduced to the cyclam molecules via a LAH reduction in low to moderate yields. Nickel incorporation into the cyclam molecules produced C-functionalized nickel catalysts with stereochemical integrity maintained throughout the synthesis. Intermolecular CH-π interactions can be seen in the solid state for the nickel cyclam complexes with aromatic side arms. Reduction data show that the C-functionalized catalysts do not show improved rates of reduction for several aromatic substrates but small rate enhancements are observed for the reduction of chloronaphthalene over the unfunctionalized catalyst.
Keywords: Cyclopeptide complexes; Cyclam complexes; Dehalogenation; Metal complexes; Chemistry, Organic (0490)